Table of Content - - (Journal of Educational and Psychological Sciences, 2025)
Table of Content:1. Measuring the level of job performance of kindergarten teachers in terms of competence (professional, educational, personal, social) in the city of MakkahAsst-Prof. Shaymah Dakhel Alluhaybi2. Requirements for transforming Taif University into a green university in light of the experiences  of the universities of Wageningen in the Netherlands, Harvard and California Berkeley in the AmericasCo-Prof. Hatim Abdullah Al-Hosiny3. The relationship of entrepreneurial leadership with the development of competitive advantage in private schools in Jeddah from the perspective of teachers and educational supervisorsMs. Shaima Fayez Al-Badri , Co-Prof. Randa Hariri4. Student Attitudes Towards Jordanian Universities - Reality and ExpectationsDr. Asma Maher Qasem5. The theoretical foundations and educational applications of pragmatist philosophy:  An analytical studyDr. Sultan Rajyan Alqathami6. Psychological Burnout among Kindergarten and First Three Grades Teachers  at Rania Governorate in Saudi ArabiaCo-Prof. Hadwa Mohmmad Salam Al-Sharari7. Irrational thoughts and their relation to the psychological stress among mothers of children  with an autism spectrum disorder in Al Majma'ah governorateMs. Manar Sayer Alotaibi